Phosphorus management and suitability of rice cultivar on system yield augmentation under rice-fallow area of Mid-Central Table Land Zone of Odisha - Prusty, M; Dash, AK; Panda, N; Satpathy, MR; Sahu, SG; Samant, PK (ORYZA-An International Journal of Rice, 2023)
A field experiment was carried out during 2018-19 and 2019-20 to study the effect of phosphorus doses and rice varieties on system efficiency in rice-green gram cropping system under Mid-Central Table Land Zone of Odisha. The experiment was conducted in split-plot design with three replications. Four main plots viz., P1: P100 of soil test dose (STD)to rice and no P to green gram, P2: P100 of STD to both the crops separately, P3 : P50 of STD to rice &P100 of STD to green gram, P4: P100 of STD of both the crops applied to rice only, were allotted to the main plots and three rice varieties viz., V1 - Mandakini, V2 - Lalat and V3 - Pratikhya to the sub plots. Application of P100 of STD to both the crops separately (P2)resulted in the highest pooled system yield of 6.87 tha-1 however amongst rice cultivars highest system yield of 6.51 t ha-1 was recorded with treatment where green gram was sown after rice cultivar "Mandakini". Similarly, thesame system P-management practice (P2) and the sowing window of rice cultivars (Mandakini) recorded the highest system nutrient uptake, gross and net returns and B: C ratio. But the available soil nutrient status was the maximum with P1 where P100 of STD as basal was applied to riceand green gram was sown after rice cv. ’Mandakini’. However, the available P of the system in the post harvest soil was estimated higher in treatment P2.